Burns and the Bank Manager: Robert Burns in the Shadow of the Debtors' Prison. (October 2015) - McGinn, Clark
<x content-type="archive" xml:space="preserve">Abstract</x> The debate about the personal 'frailties' of Robert Burns started at his death and continues today. It is common ground that the poet was never a wealthy man, but was financial management one of those personal failings? When he wrote anxious begging letters on his death bed was he in real danger of the debtors' prison, or were they the depressed thoughts of a dying man? By using the credit analytics of banking on a volume of legal papers found in the National Records of Scotland concerning Burns's estate, it is now possible for the first time to give a definitive answer to this controversy to determine if he died in debt, leaving his family unprovided and facing potential destitution.